2019
DOI: 10.1017/cts.2019.382
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of RUC-4, a novel platelet αIIbβ3 antagonist, in non-human primates and with human platelets

Abstract: Introduction: We are developing the novel αIIbβ3 antagonist, RUC-4, for subcutaneously (SC)-administered first-point-of-medical-contact treatment for ST Segment Elevated Myocardial Infarction (STEMI). Methods: We studied the: 1. pharmacokinetics (PK) of RUC-4 at 1.0, 1.93, and 3.86 mg/kg IV, IM, and SC in non-human primates (NHPs); 2. impact of aspirin on RUC-4 IC50 in human platelet-rich plasma (PRP); 3. effect of different anticoagulants on the RUC-4 IC50 in human PRP; and 4. relationship between αIIbβ3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…We previously reported that incubating whole blood with increasing concentrations of RUC-4 results in a decrease in the ability of PAC1 to bind to ADP-activated platelets, reflecting increased occupancy of αIIbβ3 receptors. 24 In the current study we assessed the effect of RUC-4 on PAC1 binding in parallel studies with both whole blood and PRP and correlated the results with the effects of RUC-4 on the VN PRUTest iso-TRAP and ADP þ PGE 1 assays and on ADP (20 µM)-induced LTA of PRP (►Fig. 2).…”
Section: Ruc-4 Produces Concentration-dependent Occupancy Of Platelet αIibβ3 Receptors That Correlates With Decreased Platelet Aggregatiomentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that incubating whole blood with increasing concentrations of RUC-4 results in a decrease in the ability of PAC1 to bind to ADP-activated platelets, reflecting increased occupancy of αIIbβ3 receptors. 24 In the current study we assessed the effect of RUC-4 on PAC1 binding in parallel studies with both whole blood and PRP and correlated the results with the effects of RUC-4 on the VN PRUTest iso-TRAP and ADP þ PGE 1 assays and on ADP (20 µM)-induced LTA of PRP (►Fig. 2).…”
Section: Ruc-4 Produces Concentration-dependent Occupancy Of Platelet αIibβ3 Receptors That Correlates With Decreased Platelet Aggregatiomentioning
confidence: 99%
“…Nonetheless, the PrSl correlates well with results based on maximal aggregation and final aggregation in the in vitro studies (►Supplementary Figure S1) and maximal aggregations in the in vivo studies. 24…”
Section: Lta Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, introducing a ring N (pyridine) yielded 15 (RUC-4), a potent antagonist (e.g., IC 50 for ADP-induced aggregation of untreated platelets is 40 ± 9 nM) that showed >60 mg/mL solubility in water with properties suitable for autoinjection . A preclinical study with this compound has been reported, and a Phase I clinical trial as potential treatment for myocardial infarction has been initiated …”
Section: Integrin Crystal Structuresmentioning
confidence: 99%